Implementing public procurement of innovations in an organization: lessons from Norway. Issue 3 (2nd September 2019) - Mwesiumo, Deodat; Olsen, Kjetil Magnus; Svenning, Geir Arne; Glavee-Geo, Richard
Abstract : Purpose: The purpose of this paper is to explore the drivers, enablers, barriers, key success factors, pitfalls and benefits of implementing public procurement of innovations (PPoI) in an organization. Design/methodology/approach: The study deployed multiple-case design, whereby six case organizations were selected according to purposeful sampling. Data collection was carried out through in-depth semi-structured one-on-one interviews with key informants. Data analysis involved coding, synthesis, categorization and aggregation. Findings: The study revealed that implementation of PPoI represents significant change in an organization, and thus, it identifies key enablers and barriers that organizations must overcome. Furthermore, the study revealed that implementation of PPoI is a necessary but not sufficient condition for reaping its benefits. Moreover, the study identified key success factors for achieving the desirable results and potential pitfalls that organizations should avoid to ensure that the execution phase is not hurt. Social implications: Overall, the findings of the study imply that PPoI and the practices associated with it are valuable to the organizations implementing it and society at large. Thus, time and financial investments and the costs associated with the challenges and barriers of implementing it are justified by the resulting wider benefits and outcomes. Originality/value: The study contributes by providing useful insights related to implementation of PPoI at an organizational level. Considering that extant literature provides limited insights on this subject, findings of this study should be of interest to researchers, public authorities, procurement practitioners, small- and medium-sized enterprises and other stakeholders. In particular, the study contributes to the body of knowledge on PPoI and offers actionable implications to both practitioners and policymakers.